1997
DOI: 10.1080/1065657x.1997.10701883
|View full text |Cite
|
Sign up to set email alerts
|

Bench-Scale Preparation of Mushroom Substrates In Controlled Environments

Abstract: Conventional composting for mushroom cultivation involves a largely uncontrolled phase in which there are wide variations in temperature and oxygen level, resulting in the production of odor pollutants. The experiments reported in this paper investigated environmental conditions for compost preparation in an attempt to minimize odor production. Substrates for mushroom culture were prepared in flasks under controlled temperature and aeration. The temperature (48 to 72°C), 0 2 concentration (0.6 to 8.7 percent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Chemical data gave a direct indication of the efficiency of conversion. Reduction in DM between raw material mixing and end of phase I was caused by microorganisms breaking down the substrate (17). Increasing ash content and EC levels, along with a fall in TSC and TSP, indicated that microbial bioconversion had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical data gave a direct indication of the efficiency of conversion. Reduction in DM between raw material mixing and end of phase I was caused by microorganisms breaking down the substrate (17). Increasing ash content and EC levels, along with a fall in TSC and TSP, indicated that microbial bioconversion had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Composts incubated anaerobically in enclosed flasks (Noble et al, 1997) produced more DMS than H 2 S at moisture contents below 73%, but proportionately more H 2 S in wetter composts (unpublished data, 1997). No effect of compost moisture content on the proportion of DMS and H 2 S emissions was found here; this may be due to variation in moisture content within large stacks.…”
Section: Discussionmentioning
confidence: 99%
“…Galls (3-5 g) from young plants were enclosed within fine mesh polyester sample bags and placed in the centre of the compost feedstocks in 2-L Quickfit multiadapter flasks (Fischer Scientific) and immersed in thermostatically controlled water baths or chambers (Noble et al ., 1997). Where required, the flasks were aerated for 2 min in every 30 min at a flow rate of 250 mL min − 1 .…”
Section: Bench-scale Flask Experimentsmentioning
confidence: 99%